Corporeità e desoggettivazione nell’estetica interculturale di Kitarō Nishida - Fongaro, Enrico (Scenari, 2021)
This essay aims to show some particular characters in the Japanese artistic tradition, through the analysis of some passages by the contemporary philosopher Kitarō Nishida (1870-1945) and the Zen master Shin’ichi Hisamatsu (1889-1980). Taking into account also some artistic experiences, such as those of ink painting, calligraphy, raku pottery or nō theater, a strong connection between aesthetics and ethics appears: art and its gestures allows in fact thanks to bodily activity a process of transformation and liberation from attachment to ego.